Respuesta :
9x^2y − 2 for x = –3 and y = 2
9 * (-3)^2 *2 − 2
= 9 * 9 * 2 - 2
= 162 -2
= 160
9 * (-3)^2 *2 − 2
= 9 * 9 * 2 - 2
= 162 -2
= 160
Step-by-step explanation:
As there are some missing signs, we can interpret this in many ways.
I will resolve all of them but the idea is the same. We have to replace the x with -3 and the y with 2.
A. 9*x*2*y-2
9*(-3)*2*2 - 2 = -108 - 2 = -110
B. 9*[tex]x^2[/tex]*y - 2
9*[tex](-3)^2[/tex]*2 - 2 = 9*9*2 - 2 = 162 - 2 = 160
C. 9*[tex]x^{2*y}[/tex] - 2
9*[tex](-3)^{2*2}[/tex] - 2 = 9*[tex](-3)^4[/tex] - 2 = 9*81 - 2 = 729 - 2 = 727